2018
DOI: 10.1111/raq.12241
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae as a sustainable aquafeed ingredient

Abstract: Macroalgae, commonly known as seaweed, offer a novel and added-value dietary ingredient in formulated diets for fish. Production of biomass can be achieved without reliance on expensive arable land, as seaweed may be collected from coastal regions or farmed. There are three taxonomic groups represented by the term 'macroalgae': Rhodophyta (red), Chlorophyta (green) and Phaeophyta (brown). Like terrestrial plants, nutritional content in macroalgae can vary greatly amongst species, genera, divisions, seasons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(154 citation statements)
references
References 258 publications
(282 reference statements)
2
149
0
3
Order By: Relevance
“…Aquaculture industry still relies on fish meal (FM) and fish oil (FO) as main protein and lipid sources for carnivorous fish species (Tacon and Metian, 2015). Macroalgae are considered an add-value ingredient due to its content on long-chain polyunsaturated acids, vitamins, minerals, pigments and antioxidant compounds, but its dietary inclusion level may be limited due to the high content of NSP (Wan et al, 2018). Indeed, high dietary level of NSP may affect the viscosity and transit velocity rate of digesta, intestinal morphology, and gut microbiota, impairing the intestinal function (Sinha et al, 2011).…”
Section: Application To the Aquafeed Industrymentioning
confidence: 99%
“…Aquaculture industry still relies on fish meal (FM) and fish oil (FO) as main protein and lipid sources for carnivorous fish species (Tacon and Metian, 2015). Macroalgae are considered an add-value ingredient due to its content on long-chain polyunsaturated acids, vitamins, minerals, pigments and antioxidant compounds, but its dietary inclusion level may be limited due to the high content of NSP (Wan et al, 2018). Indeed, high dietary level of NSP may affect the viscosity and transit velocity rate of digesta, intestinal morphology, and gut microbiota, impairing the intestinal function (Sinha et al, 2011).…”
Section: Application To the Aquafeed Industrymentioning
confidence: 99%
“…Strategic management and utilization of fish by-products shows potential for higher resource use efficiency of valuable marine resources [69]. Additionally, improvement of feed conversion ratios [2], side streams up to 30-40% of the global food system [28], and novel protein sources (microbial biomass [70], insects [71], yeast, microalgae [6], macroalgae [72], and macrophytes) might allow acceptable solutions to supplement high quality fishmeal [8,9,44]. On the other hand, farming up the food chain [Integrated Multi-Trophic Aquaculture (IMTA), biofloc aquaculture systems and aquamimicry] often require less biological resources and far less to almost no aquafeed input [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2014) stated that addition of the brown algae Ascophyllum nodosum as meals to the diet of Nile tilapia infected with A. hydrophila enhanced the sanitary status of the fish and occurrence of the infection was lower. Previous studies reported in vivo antibacterial activity of water, methanol and dichloromethane extracts of different algal species against Vibrio anguillarum, Aeromonas salmonicida, Pseudomonas anguilliseptica, A. hydrophila, Yersinia ruckeri, and shrimp Vibrio pathogens for aquaculture sanitary (Bansemir et al, 2006, Manilal et al, 2012Rizzo et al, 2017;Wan et al, 2018).…”
Section: Applications Of the Encapsulated Extracts Efficiency Of The mentioning
confidence: 99%